2022
DOI: 10.5547/01956574.43.3.pand
|View full text |Cite
|
Sign up to set email alerts
|

How May National Culture Shape Public Policy? The Case of Energy Policy in China

Abstract: This paper explores how aspects of national culture may shape the design and implementation of public policy, using the example of energy policy in China. It focuses on cognitive style and on political and legal culture. China's energy policies display a combination of pragmatism, incrementalism, internal contradiction and ambiguity. This is consistent with evidence from experimental psychology and history that the development of Chinese and East Asian cognitive styles have taken a path distinct from those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In addition, the literature [16] discusses the position of Spanish in the Chinese higher education system and also analyzes the teaching of Spanish in China, the intercultural output through the learning of Spanish and the better presentation of the Spanish image through the language. The literature [17] uses Chinese energy policy to analyze the influence of national culture on public policy and also argues that the differences between China's development in policy making and that of Western countries make it necessary to be more nuanced when formulating policy interchange between countries in cross-cultural exchange. The literature [18] investigated expatriates in China and Japan and concluded that expatriates could be better integrated into the country through cultural and linguistic identity and that multicultural development also provides new forms of work for the diversification of expatriates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the literature [16] discusses the position of Spanish in the Chinese higher education system and also analyzes the teaching of Spanish in China, the intercultural output through the learning of Spanish and the better presentation of the Spanish image through the language. The literature [17] uses Chinese energy policy to analyze the influence of national culture on public policy and also argues that the differences between China's development in policy making and that of Western countries make it necessary to be more nuanced when formulating policy interchange between countries in cross-cultural exchange. The literature [18] investigated expatriates in China and Japan and concluded that expatriates could be better integrated into the country through cultural and linguistic identity and that multicultural development also provides new forms of work for the diversification of expatriates.…”
Section: Introductionmentioning
confidence: 99%